2007
DOI: 10.1038/sj.emboj.7601616
|View full text |Cite
|
Sign up to set email alerts
|

GxxxG motifs within the amyloid precursor protein transmembrane sequence are critical for the etiology of Aβ42

Abstract: Processing of the amyloid precursor protein (APP) by b-and c-secretases leads to the generation of amyloid-b (Ab) peptides with varying lengths. Particularly Ab42 contributes to cytotoxicity and amyloid accumulation in Alzheimer's disease (AD). However, the precise molecular mechanism of Ab42 generation has remained unclear. Here, we show that an amino-acid motif GxxxG within the APP transmembrane sequence (TMS) has regulatory impact on the Ab species produced. In a neuronal cell system, mutations of glycine r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

33
421
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 270 publications
(457 citation statements)
references
References 65 publications
33
421
2
Order By: Relevance
“…In this respect, the effects of 20 μM indomethacin and 2.5 μM sulindac sulfide can be directly compared to GxxxG mutants G29A and G33A (5,7). From previous NMR measurements with purified and monodisperse C99 in lyso-myristoylphosphatidylglycerol micelles, the authors have concluded that interactions with sulindac sulfide are of nonspecific nature (15), which is seemingly in contradiction with our results obtained from the ToxR assay.…”
Section: Discussioncontrasting
confidence: 54%
See 3 more Smart Citations
“…In this respect, the effects of 20 μM indomethacin and 2.5 μM sulindac sulfide can be directly compared to GxxxG mutants G29A and G33A (5,7). From previous NMR measurements with purified and monodisperse C99 in lyso-myristoylphosphatidylglycerol micelles, the authors have concluded that interactions with sulindac sulfide are of nonspecific nature (15), which is seemingly in contradiction with our results obtained from the ToxR assay.…”
Section: Discussioncontrasting
confidence: 54%
“…For analyzing the ability of selected compounds to affect APP-TMS dimerization, we applied the well-established ToxR system using the APP-TMS residues 29-42 according to Aβ numbering ( Fig. 4A) (5,16). Briefly, this assay allows monitoring of homophilic interactions of short α-helical TMSs in bacterial membranes, as dimerization of the TMS under study is required for transcription activation of the reporter gene β-galactosidase (β-Gal) (16).…”
Section: Analysis Of Gsm-aβ Interaction By Surface Plasmon Resonance mentioning
confidence: 99%
See 2 more Smart Citations
“…Familial mutations in the APP TM region presumably affect its structure and lateral mobility in membranes; and alter proteolytic processing with the c-secretase complex. The appearance of data about possibility of APP to dimerize via specific TM helix-helix interactions [5,6] suggests a new insight on the effects of these familial mutations, implying that they could influence the APP self-association in the membrane.…”
Section: Introductionmentioning
confidence: 99%